Kemampuan Representasi Matematis Siswa Kelas VIII di Pondok Pesantren Salafiah Al-Falah Putak pada Materi Koordinat Kartesius - rama aifama rama aifama; Hartatiana Hartatiana; Harisman Nizar (JEMST (Jurnal of Education in Mathematics, Science, and Technology), 2022)
This study aims to describe the ability of students' mathematical representation in solving math problems, namely the Cartesian coordinate material. The method used in this study is a qualitative descriptive method. The subjects in this study consisted of 29 students in class VIII.5 at the Salafiah Al-Falah Putak Islamic Boarding School. Collecting research data using tests, interviews, and documentation. This study uses 3 indicators of mathematical representation ability, namely mathematical representation of images, symbol representation and verbal representation ability. The results of the study on all subjects showed that the indicators for the ability to represent mathematical images were higher with a percentage of 44% above the average, 35% for symbol representation with moderate abilities and 21% for verbal representations with low abilities. Then on the results of interviews with 6 selected subjects, namely subjects with SNT and SNS codes, they were right in solving problems given with mathematical representation indicators, but subjects with SNR codes were not so good in verbal representation skills.